The unmet drug-related needs of patients with diabetes in Ethiopia: a systematic review and meta-analysis - Gobezie, Mengistie Yirsaw; Tesfaye, Nuhamin Alemayehu; Solomon, Tewodros; Demessie, Mulat Belete; Wendie, Teklehaimanot Fentie; Belayneh, Yaschilal Muche; Baye, Assefa Mulu; Hassen, Minimize (Frontiers in Endocrinology, 2024)
Background Diabetes is a major health concern globally and in Ethiopia. Ensuring optimal diabetes management through minimizing drug therapy problems is important for improving patient outcomes. However, data on the prevalence and factors associated with unmet drug-related needs in patients with diabetes in Ethiopia is limited. This systematic review and meta-analysis aims to provide a comprehensive analysis of the prevalence of unmet drug-related needs among patients with diabetes mellitus in Ethiopia. Methods A thorough exploration of databases, including PubMed, Scopus, Hinari, and Embase and Google Scholar, was conducted to identify pertinent studies. Inclusion criteria involved observational studies that reported the prevalence of unmet drug-related needs in Ethiopian patients with diabetes. The quality of the studies was assessed using Joanna Briggs Institute (JBI) checklists. A random-effects meta-analysis was employed to amalgamate data on study characteristics and prevalence estimates, followed by subsequent subgroup and sensitivity analyses. Graphical and statistical assessments were employed to evaluate publication bias. Results Analysis of twelve studies involving 4,017 patients revealed a pooled prevalence of unmet drug-related needs at 74% (95% CI 63-83%). On average, each patient had 1.45 unmet drug-related needs. The most prevalent type of unmet need was ineffective drug therapy, 35% (95% CI 20-50). Type 2 diabetes, retrospective study designs, and studies from the Harari Region were associated with a higher prevalence. Frequently reported factors associated with the unmet drug-related needs includes multiple comorbidities, older age, and polypharmacy. Notably, the results indicated significant heterogeneity (I2 = 99.0%; p value < 0.001), and Egger’s regression test revealed publication bias with p<0.001. Conclusion The prevalence of unmet drug-related needs among diabetes patients with diabetes in Ethiopia is high with the most prevalent issue being ineffective drug therapy. Targeted interventions are needed; especially patients on multiple medications, advanced age, with comorbidities, and prolonged illness duration to improve diabetes management and outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42024501096.